ROLE OF RELIGION AND CHURCH IN SOCIAL-POLITICAL LIFE OF DEMOCRATIC SOCIETY - Липчук, О. І.; Ломака, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In this article influence of church and religious consciousness on policy and political consciousness in the conditions of development of the Ukrainian statehood when the intensity of political and religious processes has considerably accelerated is considered and their interaction amplifies. The main pressing problems of modern Ukrainian society connected with protection and realization of the religious rights and freedoms of the person and citizen in democratic society are defined. The role, value and influence of religion in the modern world on the maintenance of political life and form of the political relations is proved, comparing them with religious traditions, installations and instructions. The religion influences interaction between individuals and social groups and also between social groups. Experience of political history shows that the management of religious associations can focus directly or indirectly the flock in political affairs. Therefore the religion influences through numerous church institutions, various religious or semi-religious parties, youth, women’s, professional associations, keep an eye on the person from youth and till an old age. Through them the special role of religion in development, formation of public opinion on many political affairs is carried out. Conclusions are drawn on extent of participation and the importance of a role of religion and church in socially - political life of democratic society.